MEANING OF SIGN IN IPHONE 15 PRO (ON WITH THE SHOW) ADVERTISEMENT: ROLAND BARTHES APPROACH - Abidah, Nabila Farah; Neisyiah, Devana Nur; Afifuddin, Muzakki; Aisyah, Rasyidah Nur; Zamroni, Mohammad (JURNAL LITERASI, 2024)
This study investigates the meaning of the symbols displayed in the iPhone 15 Pro "On with the Show" advertisement on YouTube released by electronics company Apple Inc. in 2023. Apple's iPhone is considered a highly anticipated flagship product and has a strong appeal among global consumers. The focus of this research is to analyze the ad using Roland Barthes' semiotic theory, which includes the concepts of denotation, connotation, and myth. This research uses a descriptive qualitative approach using Roland Barthes' semiotic theory as the analytical framework. Data was collected through direct observation of the iPhone 15 Pro "On with the Show" advertising video as well as document analysis related to Apple Inc's marketing strategy. This method allowed the researcher to explore the symbols used in the ad and analyze the implied meaning from the perspective of semiotic theory. The analysis in this study identified several symbols that appear in the commercial, such as an angry white director with an ethnically diverse film crew, a car that explodes in a remote location, a woman driving with an alien creature, and the statement "There's no camera like Pro" with the Apple logo. Each symbol is analyzed to understand how they represent power, the challenges of action filmmaking, advanced technology, gender representation, and the image of quality associated with the iPhone 15 Pro. The findings from this study provide insights into how Apple constructs meaning and identity through its advertising, as well as how these symbols influence our perception and understanding of the product and popular culture more broadly.